Perlindungan Hukum Atas Status Kepemilikan dan Penguasaan Tanah Timbul di Desa Muarabaru Kabupaten Karawang - Risti Rahmawati; Devi Siti Hamzah Marpaung (Peneliti.net, 2023)
This research was conducted by looking at the phenomenon that occurred in Muarabaru Village, Cilamaya Wetan District, Karawang Regency where illegal land management occurred by the local community. This study uses a qualitative method with an empirical juridical approach by observing phenomena that occur in the field. The issues raised are how the legal concept of land ownership and control arises in Muarabaru Village, Karawang Regency and how legal protection for land ownership and control status arises in Muarabaru Village, Karawang Regency. This research resulted in findings in the form of raised land which is land that occurs as a result of erosion processes on the coast and management must be carried out by the state or government, even the government has the right to take back illegal management by the community, deviations occurred in Muarabaru Village where the previous village head had issued A village letter that grants land management permits to the community arises and this clearly violates the law.